Strategi Menumbuhkan Rasa Toleransi di Tengah Keberagaman Umat Desa Cisantana Cigugur-Kuningan - Imas Dariah; Gumilar Irfanullah; Umayyah Umayyah; Iksan Ghofur; Indra Gunawan (Gunung Djati Conference Series, 2023)
This study aims to discuss strategies for fostering a sense of tolerance in the midst of the diversity of the people of Cisantana Cigugur-Kuningan village. This study uses a qualitative approach with descriptive analysis method. This type of research data is qualitative data that does not use numerical statistics. The data source in this study uses secondary data sources obtained from journals, documents and articles related to the topic to be studied. Data collection techniques in this study included literature study, through journals, articles, letter magazines, and the internet. This study explains how to foster tolerance in each individual. Cisantana Village is a village that has a variety of religions embraced by its people, namely Islam, Catholicism, ADS (Djawa-Sundanese Religion), and a number of people who adhere to Hinduism and Buddhism. Even though people differ in their beliefs, they live side by side in harmony. However, as time goes by, recently there has been a conflict between Islam and the adherent religion, due to differences of opinion. Therefore, in maintaining harmony, tolerance needs to be cultivated in each individual, so that the harmony and calm that has been established for a long time will get stronger.